Analysis of Alarm in Near Field Monitor ILS Thales 421 at AirNav Semarang Branch - Novitri, Elizabeth Rindi; Eriyandi, Eriyandi (Journal of Electrical, Electronics and Informatics; Vol 8 No 2 (2024): JEEI (December 2024), 2025)
This study looks at the alarms on the Near Field Monitor ILS Thales 421 at AirNav Semarang Branch. We used a method called action research, which involves reviewing existing literature, performing corrective maintenance, and evaluating the system. The literature review helped us understand how the ILS system works and what factors can affect its performance. For corrective maintenance, we identified and fixed problems that were causing the alarms. This involved analyzing past data and observing how the system operates in real-time. After making these fixes, we evaluated how effective our actions were and what impact they had on the system's performance. Our findings showed that the alarms were triggered by several issues, including damaged cables and environmental factors. The repairs we made successfully returned the equipment to normal working conditions. Overall, this research emphasizes the importance of regular monitoring and maintenance to keep air navigation systems running smoothly. By addressing alarm issues before they escalate, we can improve the reliability and safety of air traffic management. This study provides valuable insights for those managing ILS systems, highlighting that proactive measures are key to ensuring safe and efficient operations in aviation. Air Navigation Services, Corrective Maintenance, Instrument Landing System, Nearfield Monitor